2009 6th International Conference on Electrical Engineering/Electronics, Computer, Telecommunications and Information Technolog 2009
DOI: 10.1109/ecticon.2009.5137068
|View full text |Cite
|
Sign up to set email alerts
|

A simple current-mode Schmitt trigger employing only single MO-CTTA

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…For the results as shown in Figs. 33 and 34, they are the square and triangular-waves when I B2 and I B3 = 20, 60 and 100 lA, respectively, it can be found that the output amplitudes of square and triangular-wave can be respectively tuned by I B2 and I B5 without affecting the frequency deviation, as analyzed in (30), (31) and (33). The last result is shown in Fig.…”
Section: Current-mode Triangular/square-wave Generatormentioning
confidence: 72%
See 1 more Smart Citation
“…For the results as shown in Figs. 33 and 34, they are the square and triangular-waves when I B2 and I B3 = 20, 60 and 100 lA, respectively, it can be found that the output amplitudes of square and triangular-wave can be respectively tuned by I B2 and I B5 without affecting the frequency deviation, as analyzed in (30), (31) and (33). The last result is shown in Fig.…”
Section: Current-mode Triangular/square-wave Generatormentioning
confidence: 72%
“…Furthermore, its output amplitude and threshold cannot be independently/ electronically controlled, they are also dependent on supply voltages. Afterward, the current-mode Schmitt triggers using current controlled current conveyor transconductance amplifier (CCCCTA) [32] and multiple output current through transconductance amplifier (MO-CTTA) [33] have been presented. Their features of these circuits are that the output magnitude and hysteresis levels can be controlled via electronic method.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing an input modulating signal V in with a carrier signal (triangular or saw-tooth waves) can generate a PWM signal. Previous studies have described PWM modulators based on different active building blocks [9,20,34,35]. Among them, two current tunable schemes (a sawtooth carrier-based PWM and a triangular carrier-based PWM) operated in voltagemode are designed using OTAs connected with an analog switch, a logic gate, and a few passive components [9].…”
Section: Dvcc-based Dual Mode Operation Pulse Width Modulatormentioning
confidence: 99%
“…When V o1 switches its output level from V o þ to V o À , D 1 becomes turn-off and D 2 becomes turn-on. This starts a discharging operation, causing V o2 with a linear decreasing slope expressed in (35). Utilizing the step-by-step analytic process described in Section 2.2, the expressions of the threshold levels and the peak-to-peak amplitude of the triangular wave can be derived as in Eqs.…”
Section: Extended Designs and Applicationsmentioning
confidence: 99%
“…Schmitt Triggers based on other active elements such as Current Through Transconductance Amplifier (CTTA) or Current Differencing Transconductance Amplifier (CDTA) can be found e.g. in [14], [15].…”
Section: Introductionmentioning
confidence: 99%